Development of Digital-Based Interactive E-Module on Body Measurement and Blouse Pattern Making Material at Public Vocational School - Devi, Rentya Sari; Sintawati, Esin; Kulsum, Umi; Riska, Ria (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The study aims to determine the feasibility of implementing a digital-based interactive e-module on body measurement and blouse pattern making at a public vocational school. Additionally, the study aims to determine the students' responses to the digital-based interactive e-module that covers body measurement and blouse pattern making. The development method used by the researcher refers to the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model for research development. We conducted this research at public vocational school 5 Malang. Statistical tests are carried out to change quantitative data into data that can be interpreted descriptively to determine the feasibility of digital-based interactive e-modules. The findings showed that based on the validation results from the two validators, the present digital-based interactive e-module is declared feasible and can be used in research to make it easier for students to understand learning materials. The student response questionnaire results indicated a percentage of 83.6%, which falls under the "very good" criteria; thus, the interactive e-module is considered very practical for students in class X Fashion Design and Production at Public Vocational School 5 Malang.